Assessing the Effect of Riluzole on Motor Unit Discharge Properties - Ehsan Shandiz; Gabriel Lima Fernandes; Joao Saldanha Henkin; Pamela Ann McCombe; Gabriel Siqueira Trajano; Robert David Henderson (Brain Sciences, 2024)
Background. This study aims to determine if Riluzole usage can change the function and excitability of motor neurons. Methods. The clinical data and indices of motor neuron excitability were assessed using high-density surface EMG parameters from 80 ALS participants. The persistent inward current was assessed using the discharge rate from paired motor units obtained from the tibialis anterior muscle. This enabled the discharge rate at recruitment, peak discharge rates and the hysteresis of the recruitment–derecruitment frequencies (also known as delta F) to be calculated. Limbs were classified according to their strength. Results. No differences in these motor neuron discharge properties were found according to whether Riluzole was used. Conclusions. The possible interpretations of this finding are discussed.